An Intraorganizational Ecology of Individual Attainment - Liu, Christopher C.; Srivastava, Sameer B.; Stuart, Toby E. (Organization Science, 2016)
This paper extends niche theory to develop an intraorganizational conceptualization of the niche that is grounded in the activities of organizational members. We construe niches as positions in a mapping of individuals to formal and informal activities within organizations. We posit that positional characteristics in this activity-based system are critical determinants of members’ access to information and relationships—two of the vital resources for advancement in organizations. Because activities are difficult to observe, we propose a novel empirical strategy to depict niches: we exploit a census of memberships in electronic mailing lists. We assess three niche dimensions—competitive crowding, status, and diversity—and show that these attributes affect the allocation of rewards to employees. Propositions are tested in two empirical settings: an information services firm and the R&D division of a biopharmaceutical company. Results indicate that people in competitively crowded niches had lower levels of attainment, whereas those in high status and diverse niches enjoyed higher attainment levels. We conclude with a discussion of email distribution lists as a tool for organizational research.